Artificial placentas, pregnancy loss and loss-sensitive care - Romanis, Elizabeth Chloe (Journal of medical ethics, 2024)
In this paper, we explore how the prospect of artificial placenta technology (nearing clinical trials in human subjects) should encourage further consideration of the loss experienced by individuals when their pregnancy ends unexpectedly. Discussions of pregnancy loss are intertwined with procreative loss, whereby the gestated entity has died when the pregnancy ends. However, we demonstrate how pregnancy loss can and does exist separate to procreative loss in circumstances where the gestated entity survives the premature ending of the pregnancy. In outlining the value that can be attached to pregnancy beyond fetal-centric narratives, we illustrate how pregnancy loss, separate to procreative loss, can be experienced. This loss has already been recognised among parents who have experienced an unexpected early ending of their pregnancy, resulting in their child being cared for in neonatal intensive care unit. Artificial placentas, however, may exacerbate these feelings and make pregnancy loss (without procreative loss) more visible. We argue that pregnancy is an embodied state in which gestation is facilitated by the body but gestation itself should be recognised as a process—and one that could be separable from pregnancy. In demarcating the two, we explore the different ways in which pregnancy loss can be understood. Our objective in this paper goes beyond contributing to our philosophical understanding of pregnancy towards practical-orientated conclusions regarding the care pathways surrounding the artificial placenta. We make recommendations including the need for counselling and careful consideration of the language used when an artificial placenta is used.